2017
DOI: 10.1242/dev.145441
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factors in mammalian stem cells and development

Abstract: Krüppel-like factors (KLFs) are a family of zinc-finger transcription factors that are found in many species. Recent studies have shown that KLFs play a fundamental role in regulating diverse biological processes such as cell proliferation, differentiation, development and regeneration. Of note, several KLFs are also crucial for maintaining pluripotency and, hence, have been linked to reprogramming and regenerative medicine approaches. Here, we review the crucial functions of KLFs in mammalian embryogenesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 272 publications
(263 reference statements)
5
102
0
Order By: Relevance
“…To find out which of the expression changes in RNA‐Seq experiments are the most important causes of podocyte dysfunction, we focused our attention on transcriptional factors involved in the regulation of nephrin expression and found that KLF10 is a candidate target. There are currently a total of 27 SP/KLF family members identified in mouse or human, which include nine members of the SP subfamily (SP1–SP9) and 18 members of the KLF subfamily (KLF1–KLF18; McConnell & Yang, ; Bialkowska et al , ; Memon & Lee, ). Due to the structural similarities in the SP/KLF DNA‐binding domains at their C‐terminal regions and the diverse functional (transactivation/repression) domains at their N‐terminal regions, the SP/KLF members may have overlapping sets of target genes but display diverse influences on target gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To find out which of the expression changes in RNA‐Seq experiments are the most important causes of podocyte dysfunction, we focused our attention on transcriptional factors involved in the regulation of nephrin expression and found that KLF10 is a candidate target. There are currently a total of 27 SP/KLF family members identified in mouse or human, which include nine members of the SP subfamily (SP1–SP9) and 18 members of the KLF subfamily (KLF1–KLF18; McConnell & Yang, ; Bialkowska et al , ; Memon & Lee, ). Due to the structural similarities in the SP/KLF DNA‐binding domains at their C‐terminal regions and the diverse functional (transactivation/repression) domains at their N‐terminal regions, the SP/KLF members may have overlapping sets of target genes but display diverse influences on target gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Kruppel‐like factors (KLFs) are evolutionarily conserved and structurally related zinc finger‐containing transcription factors, which also share sequence homology with specificity proteins such as SP1 and SP3 (McConnell & Yang, ; Bialkowska et al , ). Like SP subfamily members, KLFs mediate transcriptional activation and/or repression by recognizing similar GC‐rich consensus sequences in target DNA, along with the recruitment of specific co‐activators, co‐repressors, or other chromatin remodeling proteins (McConnell & Yang, ; Bialkowska et al , ). Accumulating evidence has implicated that KLFs play a vital role in multiple biological processes and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…During the first three cell cycles, we detected expression of a single Sox gene, MleSox2 (contig22607, contig22608), a member of the SoxC group (Schnitzler, Simmons, Pang, Martindale, & Baxevanis, 2014). Members of the Krüppel-like factor and specificity protein (KLF/SP) gene family are characterized by the presence of a highly conserved triple C2H2 zinc finger DNA-binding domain and play key roles in essential biological processes, including balancing stem cell proliferation and differentiation (Bialkowska, Yang, & Mallipattu, 2017;Presnell, Schnitzler, & Browne, 2015). We detected significant expression for both MleKlf5a (contig2761, contig16159, contig16164, contig26148) and MleKlf5b (contig4663, contig27551) (Presnell et al, 2015).…”
Section: Annotation Of Assembled Reference Contigsmentioning
confidence: 99%
“…cell differentiation, angiogenesis, erythropoiesis) 1113 . Recent studies demonstrate that KLFs play a vital role in cardiac, liver, and kidney fibrosis 1113 .…”
Section: Introductionmentioning
confidence: 99%
“…cell differentiation, angiogenesis, erythropoiesis) 1113 . Recent studies demonstrate that KLFs play a vital role in cardiac, liver, and kidney fibrosis 1113 . Specifically, the global loss of KLF15 exacerbated interstitial fibrosis in 5/6 nephrectomized rats 14, 15 .…”
Section: Introductionmentioning
confidence: 99%